2016
DOI: 10.1016/j.jtho.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Lung Adenocarcinoma Biomarker in a Caribbean and African Caribbean Population

Abstract: Patients in Martinique, and specifically those of African descent, show very high levels of EGFR mutation as opposed to what can be found in mainland France or in African Americans. These findings may be ascribed to low tobacco consumption as well as to genetic factors. Systematic screening in patients of African Caribbean origin should be prescribed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Clifford et al reviewed those controversial reports, pointing at some potential reasons: population bias concerning sex, smoker status and self-reporting ethnicity, disparity in technological approaches used to detect mutations as well as Simpson's paradox, which is the statistical correlation observed in aggregated heterogeneous groups which could be reversed when groups are disaggregated [35]. Moreover, in a recent study in Caribbean populations, mostly African descendent, Leduc et al found EGFR mutations in 36% of patients, which is higher than expected [36]. The authors ascribed their finding to environmental factors such as low tobacco consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Clifford et al reviewed those controversial reports, pointing at some potential reasons: population bias concerning sex, smoker status and self-reporting ethnicity, disparity in technological approaches used to detect mutations as well as Simpson's paradox, which is the statistical correlation observed in aggregated heterogeneous groups which could be reversed when groups are disaggregated [35]. Moreover, in a recent study in Caribbean populations, mostly African descendent, Leduc et al found EGFR mutations in 36% of patients, which is higher than expected [36]. The authors ascribed their finding to environmental factors such as low tobacco consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The most common NSCLC histological phenotypes are lung adenocarcinoma (LADC, ∼50% of patients) and lung squamous cell carcinoma (LSCC, ∼40% of patients) [ 1 ]. LADC cells commonly exhibit abnormal gene expression patterns and large numbers of gene mutations [ 2 ], and are characterized by specific biomarkers[ 3 7 ] and prognostic factors [ 8 10 ] that can be used to guide clinical diagnosis and treatment. LSCC cells also exhibit complex genomic alterations, including numerous gene mutations and copy number alterations [ 11 ], and are associated with particular biomarkers [ 12 14 ] and prognostic factors [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, birthplace was not an independent factor in mutation in the multivariate analysis. 1 In our opinion, this study finding raises an important question. Which epidemiological factors could have the most influence on EGFR mutation frequency: ethnic differences, smoking status, sex, or age of the patient?…”
Section: To the Editormentioning
confidence: 77%
“…We read with great interest the article of Leduc et al titled "Incidence of Lung Adenocarcinoma Biomarker in a Caribbean and African Caribbean Population." 1 In this work, the authors retrospectively identified targetable biomarkers in Caribbean patients with lung adenocarcinoma, including EGFR gene mutations.…”
Section: To the Editormentioning
confidence: 99%